The role of culture in the development of eating disorders with special attention to anorexia nervosa and bulimia nervosa - Bauchinger, Iris Maria (University of the Free State, 2002)
𝑬𝒏𝒈𝒍𝒊𝒔𝒉 This study is an exploratory, empirically based investigation into the connection between culture and anorexia nervosa and bulimia nervosa as found in three selected female groups. The specific objectives of the research were to obtain perceptualconceptual information concerning the individual's experience of her self and the body image; to investigate the influence of familial factors such as the family environment, parent-child relationship, parental styles, discourses on weight, food consumption, and lifestyle present in the family; and to examine popular cultural influences, like the pressure for thinness expressed by peer groups and the visual as well as printed media. The literature study included subjects such as the relationship between food and culture; the history, characteristics of and approaches to anorexia nervosa and bulimia nervosa; beauty standards and the fear of obesity in the Western culture; and the nature and influence of socialisation agents. The empirical research was carried out among 24 Caucasian females between the ages of 14 and 28. Three different groups were formed with Group 1 consisting of females already diagnosed with an eating disorder; Group 2 comprising young females working part-time or full-time for a model agency; and Group 3 comprising young females who are members of a dance school. Quantitative research information was obtained through the use of three standardised questionnaires, namely the Body Shape Questionnaire (BSQ), the Socio-cultural Attitudes Towards Appearance Questionnaire (SATAQ), and Eating Attitudes Test (EAT 40). However, the main emphasis in data gathering was qualitative in nature. For this purpose, a structured questionnaire was drawn up to obtain information on cultural influences. This was followed by semi-structured, in-depth interviews with all the research participants. Results of the analysed data revealed that the participants have a thorough knowledge on calorie intake, dieting and various methods of controlling weight. All the participants are preoccupied and dissatisfied with their body size and shape. They have an almost irrational fear of obesity and go to extreme lengths to maintain a slim and slender physique. Consciously or unconsciously, they all acknowledge the ideological influence of the Western ideal of thinness, which is transmitted, in equal intensity by family, peers and the media. Assumptions that women should eat less than men and watch their weight are rooted in the family experiences of most participants. This deep-seated belief in restraining women consequently influences the participants to model weight conscious behaviours practised in the family home. In order to conform to the societal pressure to be thin and to attract male counterparts, the participating girls also encourage each other to lose weight by suggesting dieting behaviour. Competitions are held between peers regarding the most attractive female physique and teasing behaviour is said to occur in the event of girls not achieving the ideal. In addition to family and peer influences, the media also enhances behavioural modelling by presenting a largely unattainable ideal of the thin, beautiful, successful superwoman. Participants idealise and glorify the slender ideal and stars' and fashion models' bodies presented on television and in magazines are the ultimate in preferred physiques. In addition, dietary products advertised by the media are often bought and seen as the last solution in the ongoing struggle to be slim. The essential conclusion is that eating/body problems among Western women cannot be understood outside the cultural settings in which they occur and will not be solved unless cultural agents like the family, peers and the media undergo a paradigm shift regarding the dangerous side of the slender female body ideal. ___________________________________________________________________

𝑨𝒇𝒓𝒊𝒌𝒂𝒂𝒏𝒔 Die studie is 'n verkennende, empiriese ondersoek na die verband tussen kultuur en anorexia nervosa en bulimia nervosa soos bevind in drie geselekteerde groepe vroue. Die spesifieke doelwitte van die navorsing was om perseptueel-konseptuele inligting te bekom aangaande die indiwidu se ervaring van haar self- en liggaamsbeeld; om ondersoek in te stel na die invloed van gesinsfaktore soos die gesinsomgewing, ouerkind-verhouding, ouerskapstyle, gesprekke oor liggaamsmassa, eetgewoontes en die lewenstyl van die gesin, asook om algemene kultuurinvloede, by voorbeeld die druk om 'n skraal liggaamsbou te hê, soos voorgehou deur portuurgroepe en die visuele en gedrukte media, te ondersoek. Die literatuurstudie dek onderwerpe soos die verhouding tussen voedsel en kultuur; die geskiedenis, kenmerke van en benaderings tot anorexia nervosa en bulimia nervosa; skoonheidstandaarde en die vrees wat betref vetsug in die Westerse kultuur; en die aard en invloed van sosialisieringsagente. Die empiriese ondersoek is onderneem met 24 Kaukasiese meisies met ouderdomme wat wissel tussen 14 en 28 jaar. Drie afsonderlike groepe is gevorm, met Groep 1 bestaande uit persone wat reeds gediagnoseeer is met 'n eetversteuring; Groep 2, bestaande uit jong meisies wat voltyds of deeltyds vir 'n modelagentskap werk; en Groep 3, bestaande uit jong meisies wat lede van 'n dansskool is. Kwantitatiewe navorsingsinligting is verkry deur drie gestandaardiseerde vraelyste te gebruik, naamlik die Body Shape Questionnaire (BSQ), die Socio-cultural Attitudes Towards Appearance Questionnaire (SATAQ) en die Eating Attitudes Test (EAT 40). Die hoofdoel was egter om kwalitatiewe inligting te bekom, en vir die doel is 'n gestruktueerde vraelys opgestel om inligting te bekom aangaande kultuurinvloede. Hierna is semi-gestruktureerde in-diepte onderhoude met al die deelnemers aan die navorsingsprojek gevoer. Resultate van die geanaliseerde data het getoon dat die deelnemers 'n deeglike kennis het van kalorie-inname, diëte en verskeie metodes om liggaamsmassa te beheer. Al die deelnemers was oormatig bekommerd oor en ontevrede met die grootte en vorm van hul liggame. Hulle het 'n byna irrasionele vrees vir vetsug en gaan tot uiterste handelinge oor om 'n tenger en slanke liggaamsbou te handhaaf. Bewustelik of onbewustelik gee hulle almal erkenning aan die ideologiese invloed van die Westerse ideaal van skraalheid, wat in gelyke mate oorgedra word deur familielede, portuurgroepe en die media. Aannames dat vroue minder as mans behoort te eet en hul massa moet beheer het hulontstaan in die gesinservaringe van die meeste deelnemers. Hierdie diepgesetelde opvattinge rakende die inperking van vroue beïnvloed gevolglik die deelnemers om die massabewustheidsgedrag van hul gesinsgenote net so as die norm te aanvaar. Om te konformeer aan die gemeenskapsdruk om skraal te wees en om manlike aanhangers aan te trek, moedig die deelnemende meisies mekaar aan om gewig te verloor deur diëte te volg. Kompetisies word gehou tussen portuurgroepe om te bepaal wie die aantreklikste liggaam het, en meisies wat nie die ideale liggaamsbou bereik nie, word geterg. Tesame met die invloed van die gesin en portuurgroep, dra die media ook by tot die navolgingsgedrag deur 'n feitlik onbereikbare ideale supervrou met 'n pragtige skraal lyf uit te beeld. Deelnemers idealiseer en verheerlik die slanke uiterlike voorkoms en die liggame van filmsterre en mannekyne wat in tydskrifte of op televisie voorgehou word. Daarby word vele verslankingsmiddels en dieetprodukte wat deur die media geadverteer word, gekoop as 'n laaste uitweg in die ewigdurende stryd om skraal te wees. Die kern gevolgtrekking wat gemaak word is dat eet- en liggaamsprobleme onder Westerse vroue nie buite hulle kulturele agtergrond verstaan kan word nie, en dat probleme ook nie opgelos kan word, tensy kulturele agente soos die gesin, portuurgroep en die media 'n paradigmaskuif ondergaan rakende die gevaarlike kant van die skraal vroulike liggaamsideaal nie. ___________________________________________________________________
Dissertation (M.Soc.Sc.(Anthropology))--University of the Free State, 2002
Keywords: Food as culture; Socialisation; Multi-media; Body image; Weight control; Dieting; Eating disorders; Anorexia nervosa; Bulimia nervosa; Culture-bound syndrome; Eating disorders; Self-perception in women; Medical anthropology